Kinerja Dokter Muda sebagai Mediasi Pengaruh Burnout, Kecerdasan Emosional, Self-efficacy terhadap Kepuasan Kerja di Rumah Sakit dr. Soetomo Surabaya, Indonesia - Raden Andi Sularso (Universitas Proklamasi 45 Yogyakarta, 2018)
Job satisfaction and performance of co-assistant doctors can not be separated by burnout, given the high mobility of work in clinical studies and assisting clinical lecturers in serving patients. Burnout is a psychological syndrome consisting of three dimensions, namely emotionalexhaustion, depersonalization, and low personal accomplisment. To achieve the performance and job satisfaction of young physicians with intervening emotional intelligence and self-efficacy can anticipate burnout. This study includes the type of explanatory research with cross-sectional data collection method. The sample size is the same as the population of 270 co-assistants with the Generalized Structured Component Analysis (GSCA) method. The results of this study found that from seven direct effects between the variables tested, there are five significant effects that are: (1) burnout have a significant effect on emotional intelligence; (2) burnout have a significant effect on self-efficacy; (3) self-efficacy have a significant effect on emotional intelligence; (4) emotional intelligence has a significant effect on performance, and (5) self-efficacy has a significant effect on performance, while (1) burnout has no significant effect on self-efficacy; and (2) co-assistant performance has no significant effect on co-assistant doctor job satisfaction.